Expression of a carotenoid‐modifying gene and evolution of red coloration in weaverbirds (Ploceidae) - Hanlu Twyman; Maria Prager; Nicholas I. Mundy; Staffan Andersson (Molecular Ecology, 2018)
Red carotenoid colours in birds are widely assumed to be sexually selected quality indicators, but this rests on a very incomplete understanding of genetic mechanisms and honesty‐mediating costs. Recent progress was made by the implication of the gene CYP2J19 as an avian carotenoid ketolase, catalysing the synthesis of red C4‐ketocarotenoids from yellow dietary precursors, and potentially a major mechanism behind red coloration in birds. Here, we investigate the role of CYP2J19 in the spectacular colour diversification of African weaverbirds (Ploceidae), represented by five genera and 16 species: eight red, seven yellow and one without carotenoid coloration. All species had a single copy of CYP2J19 , unlike the duplication found in the zebra finch, with high expression in the retina, confirming its function in colouring red oil droplets. Expression was weak or undetected in skin and follicles of pigment‐depositing feather buds, as well as in beaks and tarsi, including those of the red‐billed quelea. In contrast, the hepatic (liver) expression of CYP2J19 was consistently higher (>14‐fold) in seven species with C4‐ketocarotenoid coloration than in species without (including one red species), an association strongly supported by a phylogenetic comparative analysis. The results suggest a critical role of the candidate ketolase, CYP2J19, in the evolution of red C4‐ketocarotenoid colour variation in ploceids. As ancestral state reconstruction suggests that ketocarotenoid coloration has evolved twice in this group (once in Euplectes and once in the Quelea / Foudia clade), we argue that while CYP2J19 has retained its ancestral role in the retina, it has likely been co‐opted for red coloration independently in the two lineages, via increased hepatic expression.